Introduction to the Alexander technique a practical guide for actors - Connington, Bill 1958- (Meuthen Drama, 2020)
Introduction to the Alexander Technique is the first textbook about the Alexander Technique written specially for undergraduates. Part of the Acting Essentials series, this eight-week program can be taught over the course of half a semester, a full semester, or dipped into as needed to address students' issues with physicality, movement, breathing, voice and performance habits. The Alexander Technique has been a vital part of training for performers since the early 20th century. It is a core part of the curriculum at most acting conservatories and in many BFA programs. Sometimes considered purely a movement discipline, the Alexander Technique in fact takes into consideration the entire person--mind, body, emotions, and imagination. Introduction to the Alexander Technique addresses the student's self as a whole and is suitable for beginning acting students in any academic setting, including those who take performance classes as an elective. The book also includes more than 150 practical, easy-to-follow exercises that help students reduce tension and improve their alignment, flexibility and poise. The textbook is supported by a range of online videos demonstrating key exercises described throughout the book"--